(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Bestlink College of the Philippines’ practical laboratory trends are fully air-conditioned, well-ventilated, good ambiance, and taking good care in the working environment to make the students feel comfortable. The issue is that the practical laboratories in BSHM have limited water, and not all equipment is available. In this issue, the students lose proper coordination and momentum in their practical laboratory. One of the problems that the students face is limited time, school following rules and orders to the higher-ups, and clogged sinks. Based on the study outcome, practical laboratory helps the students improve their skills. The school will provide more tools and equipment for a better experience, which will help their future career. The respondents recommend expanding the working area to cater to all the students during their practical output. The faculty should discuss adding more time in the practical laboratory for the students to have better learning and should request the program head or school to provide more tools and equipment that will help them provide quality education. Schools should have better scheduling to avoid water problems during the laboratory. Schools need to provide more sizes of uniforms (PPE) available for all that will keep the students out of harm during the practical laboratory. The school should always prepare a planning meeting for the students, teachers/professors, and the rest of the HM department. The school should fix the working ergonomics of the facilities. The result of the study would be a great help to the school in considering providing more tools and equipment to improve facilities that will encourage the student to learn more and enhance their skills in their specialization.